2021
DOI: 10.1115/1.4049885
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation: Examining the Complex Relationship Between Prototyping and Communication

Abstract: Prototyping plays a pivotal role in the engineering design process. Prototypes represent physical or digital manifestations of design ideas, and as such act as effective communication tools for designers. While the benefits of prototyping are well-documented in research, the fundamental ways in which the construction of a prototype affects designers' reflection on and evaluation of their design outcomes and processes are not well understood. The relationships between prototypes, designers' communication strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Therefore, within the pitch, the role of the prototype evolved and the design team leveraged the prototype to both explain and justify their solution. In future work, we aim to uncover the manner in which students justify, or rationalize, their design outcomes, as prior work suggests novice designers tend to distance themselves from failures in prototyping tasks, and attribute these failures to external factors, such as a scarcity of time or resources (Krishnakumar et al, 2021). Through our preliminary results, we note some similarities in how novices and experts use prototypes to explain design outcomes and persuade audiences about the success and effectiveness of the design outcome.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, within the pitch, the role of the prototype evolved and the design team leveraged the prototype to both explain and justify their solution. In future work, we aim to uncover the manner in which students justify, or rationalize, their design outcomes, as prior work suggests novice designers tend to distance themselves from failures in prototyping tasks, and attribute these failures to external factors, such as a scarcity of time or resources (Krishnakumar et al, 2021). Through our preliminary results, we note some similarities in how novices and experts use prototypes to explain design outcomes and persuade audiences about the success and effectiveness of the design outcome.…”
Section: Discussionmentioning
confidence: 85%
“…Prior work has demonstrated that novices tend to see prototyping primarily as a method to evaluate the functionality of a design solution (Deininger et al, 2017;Lauff et al, 2017). Recent work by Krishnakumar et al (2021) also suggests that novice designers struggle to rationalize their design decisions after a prototyping task, often attributing failure to external factors and employing a number of rhetorical strategies to justify their design solution.…”
Section: Prototypes As Communication Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criticality of design artefacts to the design process more broadly, and to design communication more specifically, is well documented (Krishnakumar et al, 2021). Sketches, prototypes, and digital models can help designers build a shared understanding of the design space.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined how engineering design language is used to communicate design work and how this language evolves over time during undergraduate and practitioner settings [14][15][16][17][18] even finding that effective argumentation can result in improved designs [19]. There are multiple forms of communication that are used to advocate for a design, such as linguistic cues [25,26], engagement with props and prototypes [20][21][22][23][24], written reports [27][28][29][30], and gestures [31]. However, students are typically only taught communication through a few traditional methods.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%